Role of Multidetector CT Imaging in the Risk Stratification of Gastrointestinal Stromal Tumors (GISTs)-A Retrospective Analysis - Geena Benjamin; Thara Pratap; Mangalanandan Sreenivasan; Dhanya Jacob; Agnes Thomas; Bala Sankar; Amith Itty (Thieme Medical and Scientific Publishers Pvt. Ltd., 2021)
Background Gastrointestinal stromal tumors (GISTs) are the most common gastrointestinal mesenchymal neoplasms which can arise from any part of the gastrointestinal tract (GIT) or an extraintestinal location. Size and the organ of origin are the major imaging inputs expected from the radiologist. However, it is worthwhile to find out which imaging characteristics on MDCT correlate with risk stratification. This knowledge would help the clinician in treatment planning and prognostication. The aim of this retrospective study is to evaluate the various MDCT imaging characteristics of GISTs and find out which parameters have significant association with risk and subsequent development of metastasis on follow-up whenever it was possible. Materials and Methods This is a retrospective study conducted on 45 histopathologically proven cases of GIST from two institutions by searching from the digital archives. The following imaging parameters were analyzed: maximum size in any plane, organ of origin, shape (round, ovoid or irregular), margin (well-defined or ill-defined), surface (smooth or lobulated), percentage of necrosis, growth pattern, enhancement characteristics-both intensity (mild, moderate or significant) and pattern (homogenous vs. heterogenous), calcification, infiltration into adjacent organs, and presence of metastasis at presentation or on follow-up. Results CT morphological parameters of significance in risk stratification as per our study include tumor necrosis, predominant cystic change, irregular and lobulated shape/surface characteristics, and adjacent organ infiltration. The parameters which were associated with development of metastasis were size > 5 cm, necrosis > 30%, and the presence of adjacent organ infiltration. Conclusion The radiologist has an important role in ascertaining the size of tumor as well as the organ of origin accurately to guide the clinician in risk calculation and subsequent prognostication. In addition, certain CT characteristics mentioned above, namely, tumor size, significant necrosis/cystic changes, irregular/lobulated contour, and invasion of adjacent organs, help in risk stratification and in predicting metastasis/poor prognosis.